2021
DOI: 10.1016/j.carbon.2020.10.030
|View full text |Cite
|
Sign up to set email alerts
|

On the role of impurities on spheroidal graphite degeneracy in cast irons

Abstract: Though manufacturing spheroidal graphite cast irons is a well established industrial process, good nodularity which is essential for mechanical properties rnay be hampered by several factors. Arnongst them is the presence of impurities at trace level which lead to the growth of protrusions and the question is how they can destroy the spheroidizing effect of rnagnesium For the first time, it is shown that such impurities are present together with magnesium at the int erface between spheroid and protrusion. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, it was challenged in the mid-1970s when Auger spectroscopy measurements failed to detect magnesium on graphite spheroids [26]. Advances in microanalysis have revealed the presence of magnesium in some cases but have also confirmed the absence of accumulation of this element at the graphite/matrix interface [27][28][29]. The lack of detection by Auger mentioned above would therefore be due to the detection limit of this technique (a few %) in the presence of a more diluted spatial distribution of magnesium than imagined.…”
Section: Role Of Magnesiummentioning
confidence: 99%
“…However, it was challenged in the mid-1970s when Auger spectroscopy measurements failed to detect magnesium on graphite spheroids [26]. Advances in microanalysis have revealed the presence of magnesium in some cases but have also confirmed the absence of accumulation of this element at the graphite/matrix interface [27][28][29]. The lack of detection by Auger mentioned above would therefore be due to the detection limit of this technique (a few %) in the presence of a more diluted spatial distribution of magnesium than imagined.…”
Section: Role Of Magnesiummentioning
confidence: 99%
“…In fact, low level of Mg at the interface was detected after heat-treatment of the casting [4,5] while it was not in the as-cast state, suggesting absorption of Mg during growth and later expulsion as graphite crystallinity increases. In the case of slow cooling casting, Mg could be detected within graphite and sometimes accumulated at the graphite matrix using EDS in a SEM on FIB thinned lamellae [59]. Using both atom probe and EDS in a TEM, Qing et al showed the presence of many foreign elements in graphite amongst which Mg and Ce [60].…”
Section: Interfacial Segregationmentioning
confidence: 99%
“…Using EDS in an atomic resolution microscope, Domengès et al could also observe compounds of Mg, Sn and Pb at the interface between a spheroid and a protuberance [59].…”
Section: Shape Of Primary Graphitementioning
confidence: 99%
“…While the vast majority of metal materials can be recycled through re-melting processes, the economics of scale and inefficient sorting techniques often result in the incorporation of contaminants. These impurities, seemingly innocuous in their trace quantities, can have a profound impact on both mechanical properties and machinability of finished and semi-finished metal products [3,4,5].…”
Section: Introductionmentioning
confidence: 99%